2010
DOI: 10.1165/rcmb.2009-0138oc
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Alveolar Epithelial Translocation of a Defined Population of Nanoparticles

Abstract: To explore mechanisms of nanoparticle interactions with and trafficking across lung alveolar epithelium, we utilized primary rat alveolar epithelial cell monolayers (RAECMs) and an artificial lipid bilayer on filter model (ALBF). Trafficking rates of fluorescently labeled polystyrene nanoparticles (PNPs; 20 and 100 nm, carboxylate (negatively charged) or amidine (positively charged)-modified) in the apical-to-basolateral direction under various experimental conditions were measured. Using confocal laser scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
146
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(151 citation statements)
references
References 50 publications
(68 reference statements)
2
146
3
Order By: Relevance
“…Yacobi et al studied the mechanisms of nanoparticle interactions with lung alveolar epithelium during translocation utilizing rat alveolar epithelial cell monolayers (RAECM). Polystyrene nanoparticles of size 20-100 nm appeared to translocate across RAECM in the apical to basolateral direction transcellularly, primarily via nonendocytic pathways with direct involvement of the lipid in the cell's plasma membrane (51). The results also suggested that 20 nm particles transport twofold to threefold faster than 100-120 nm particles of similar charge while positively charged particles translocated 20-to 40-fold faster than negatively charged particles.…”
Section: Translocation Of Inhaled Medication To Blood Circulationmentioning
confidence: 86%
“…Yacobi et al studied the mechanisms of nanoparticle interactions with lung alveolar epithelium during translocation utilizing rat alveolar epithelial cell monolayers (RAECM). Polystyrene nanoparticles of size 20-100 nm appeared to translocate across RAECM in the apical to basolateral direction transcellularly, primarily via nonendocytic pathways with direct involvement of the lipid in the cell's plasma membrane (51). The results also suggested that 20 nm particles transport twofold to threefold faster than 100-120 nm particles of similar charge while positively charged particles translocated 20-to 40-fold faster than negatively charged particles.…”
Section: Translocation Of Inhaled Medication To Blood Circulationmentioning
confidence: 86%
“…To explore if quantum dot translocation across RAECM involves endocytotic mechanisms, methyl-β-cyclodextrin, chlorpromazine, and dynasore were used to disrupt lipid raft-mediated endocytosis, 30,32,36,37 clathrin-mediated endocytosis, 30,38 and dynamin-dependent endocytosis (including clathrin-mediated and caveolin-mediated endocytosis), 30,32,39 respectively. Briefly, RAECM were pretreated for 30 minutes with methyl-β-cyclodextrin (200 µM, Sigma), chlorpromazine (28 µM, Sigma), or dynasore (80 µM, Sigma) in both apical and basolateral fluids.…”
Section: Effects Of Endocytosis Inhibitorsmentioning
confidence: 99%
“…[24][25][26][27][28][29] It is currently thought that both the size and surface properties of nanoparticles affect the cytotoxicity and intracellular fate(s) of nanoparticles. [30][31][32][33] In this regard, we recently reported the trafficking properties of polystyrene nanoparticles with variable sizes and surface charges across RAECM. 30,31 In brief, trafficking rates of polystyrene nanoparticles across RAECM are dependent on both surface charge density and size, in that we found an approximately 20-40 times greater flux for positively (versus negatively) charged polystyrene nanoparticles of similar size and that larger polystyrene nanoparticles (about 100 nm) cross RAECM about 3-4 times slower than smaller polystyrene nanoparticles (20 nm) of similar surface charge.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations